2005
DOI: 10.1124/mol.105.016832
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Organic Cations with a Newly Identified Plasma Membrane Monoamine Transporter

Abstract: Many endogenous compounds and xenobiotics are organic cations that rely on polyspecific organic cation transporters (OCTs) to traverse cell membranes. We recently cloned a novel human plasma membrane monoamine transporter (PMAT) that belongs to the equilibrative nucleoside transporter (ENT) family. We have reported previously that, unlike other ENTs, PMAT (also known as ENT4) is a Na ϩ -independent and membrane potential-sensitive transporter that transports monoamine neurotransmitters and the neurotoxin 1-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
196
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(210 citation statements)
references
References 31 publications
(61 reference statements)
10
196
3
Order By: Relevance
“…Other chemical inhibitions rule out the involvement of the choline transporters, PMAT, and carnitine transporters, OCTN2-3 (Inazu et al, 2005;Wu et al, 1999). Moreover, PMAT is sensitive to the trans-membrane potential and is inhibited by dopamine, histamine, and cimetidine (Engel et al, 2004;Engel and Wang, 2005;Xia et al, 2007). Thus, these experiments suggest that clonidine transport at the mouse luminal BBB is mediated by a new organic cation/H + antiporter, as suggested in other cells (Fischer et al, 2006(Fischer et al, , 2007.…”
Section: Discussionsupporting
confidence: 53%
“…Other chemical inhibitions rule out the involvement of the choline transporters, PMAT, and carnitine transporters, OCTN2-3 (Inazu et al, 2005;Wu et al, 1999). Moreover, PMAT is sensitive to the trans-membrane potential and is inhibited by dopamine, histamine, and cimetidine (Engel et al, 2004;Engel and Wang, 2005;Xia et al, 2007). Thus, these experiments suggest that clonidine transport at the mouse luminal BBB is mediated by a new organic cation/H + antiporter, as suggested in other cells (Fischer et al, 2006(Fischer et al, , 2007.…”
Section: Discussionsupporting
confidence: 53%
“…It has also been demonstrated that in hypothalamus, corpus callosum and optic nerves of rat brain, 5-HT uptake under Na + -free condition accounted for about 20% of total uptake, and fluoxetine, a potent inhibitor of SERT, only caused a 57% decrease in 5-HT uptake [28]. Most recently, a study reported that local perfusion of decynium 22, a high affinity inhibitor of OCT and PMAT (K i = 0.1 μM) [29], resulted in a significant, dose-dependent increase in extracellular 5-HT level in rat dorsomedial hypothalamus where SERT is minimally expressed [25]. Therefore, PMAT, together with the OCTs, may play a significant role in 5-HT clearance in brain regions where expression of SERT is low or when SERT function is pharmacologically inhibited, such as chronic use of antidepressants.…”
Section: Discussionmentioning
confidence: 98%
“…The plasma membrane monoamine transporter (PMAT; SLC29A4), identified in 2004, accepts structurally diverse hydrophilic organic cations as substrates, such as 1-methyl-4-phenylpyridinium (MPP + ), tetraethylammonium, serotonin, dopamine, epinephrine, norepinephrine, guanidine, and histamine 34,35 . In immunofluorescence studies 36 ,Xia et al showed that PMAT is primarily targeted to the apical membrane of polarized epithelial cells .…”
Section: Transporters Involved In Metformin Intestinal Absorptionmentioning
confidence: 99%